Analisis Faktor yang Menyebabkan Downtime pada Mesin Injector Freon di Divisi Refrigerator PT. XYZ - Achmad Azis Rahmanto; Rifki Irfani; Lazuardi Allan Suryawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
The freon injector machine is a crucial component in the production line at PT. XYZ, responsible for refrigerant injection. However, frequent downtime disrupts production efficiency. This study aims to analyze the factors causing downtime in the freon injector machine at PT. XYZ, focusing on Coupler component failures. Using the PDCA method and fishbone diagram analysis, the primary causes were identified across human, method, machine, and material factors. Installation and removal errors contributed to human-related issues, while the absence of preventive maintenance resulted in reactive component replacement. Machine-related factors included component wear and latch failure, whereas material-related issues stemmed from a lack of understanding of load limits, leading to faster wear. The SMART method was used to validate corrective measures. Implementing better maintenance strategies, including scheduled preventive maintenance and increased technician awareness, is expected to significantly reduce downtime and enhance production efficiency.